(Review) Xu, J.J. (eds.) (2022). Tiyu Yingyu Cihui Shouce (The Wordbook of Sports English). Beijing: Foreign Language Teaching and Research Press - Chen, Xi (International Journal of Linguistics, 2023)
In this article, the advantages and disadvantages of Tiyu Yingyu Cihui Shouce (The Wordbook of Sports English), a recently published corpus-based English wordbook related to sports, will be reviewed and discussed. This wordbook has some highlighting features including vocabulary and example sentences based on sports-related corpus, especially Olympic-related corpus which displays some encyclopedic information about the Olympic Games especially the Olympic Winter Games Beijing 2022 in both content and appendixes. To cater to mobile learning, the book integrates all the headwords into the smartphone application, which offers multiple ways to memorize vocabulary. However, this book has something that needs to be improved in the following edition, including the unclearness of icons which indicates the usage scenario, lack of the function to review previous learning, translation of some entries, etc. In general, this wordbook is a useful tool for those who want to learn words about sports in China.